Rancang Bangun Sistem Pakar Backward Chaining Untuk Antisipasi Hama Tumbuhan Kedelai - Resnawita, R; Siregar, Diffri Solihin; Adawiyah, Quratih; Defit, Sarjon (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Soybeans are an important source of protein in Indonesia. Soybean cultivation in Indonesia faces difficulties posed by climate-related elements that create an ideal environment for the proliferation of various pest species, including those that attack leaves and pods. An expert system is a computing system designed to replicate all aspects of expert capacity in decision making. The Backward Chaining method is an approach where the reasoning process begins with the goal or conclusion to be achieved. This research aims to build a system to provide anticipation in dealing with soybean plant diseases and pests. The results of this expert system research support consultations by uploading photos as a consultation medium. Administrators have the ability to manage soybean crop data in the knowledge base, including adding, editing, and deleting data. The expert system is able to display diagnoses accompanied by complete prevention and management solutions for identified symptoms